Efficacy of Hip Abductors Strengthening as Compared to Piriformis Muscle Stretching in Improving Lower Extremity Function in Patients with Piriformis Syndrome - Kinza Idrees, Khalid Khan, Khadija Sharif, Khadija Ahmad, Hamna Rahman, Farzana Fahad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study's goal was to determine the effects of hip abductors strengthening and piriformis stretching on pain, hip abductors strength, and lower extremity functional status in piriformis syndrome patients. Methodology: A total of 60 patients were diagnosed with piriformis syndrome and referred to the Physiotherapy department from the NILD Assessment Clinic. Then, using simple random sampling, 60 patients were divided into two groups: Group-A (Hip abductor and Sciatic nerve mobilisation) and Group-B (no hip abductor and sciatic nerve mobilisation) (Sciatic nerve mobilisation and piriformis stretching). Each subject's demographic data was collected prior to the intervention. Data on pain severity, muscle strength (hip extensor and abductor), and lower extremity functional scale score were collected before and after treatment. Both groups continued to take their medications according to the evaluation clinic's recommendations. Results: Patient’s average age was 57.18 ± 2.64 years. Out of 60 patients 19 belongs to age 35-45 year, 13 belongs to 45-55 year and 28 belongs to age group of 55-65 year. This table explains that mean difference of NPRS and Hip Abductor strength between two groups showed p-value 0.082 and 0.100 respectively statistically non-significant result, whereas, Hip Abductor strength and LEFS showed p-value 0.001 statistically significant difference between two groups. Conclusion: According to the findings piriformis syndrome can be treated without the use of stretching, electrophysical agents, or soft tissue mobilization. Considering that piriformis insertion is on greater trochanter. The excessive hip adduction and internal rotation shown during functional movement testing were exerting tension on this muscle, resulting in sciatic nerve compression. However only Group A improved in terms of hip abductor strength. Group A demonstrated considerable improvement in strength of hip abductor and lower extremity functional scale when compared to Group B. Keywords: Piriformis syndrome, Sciatica,